Shari'ah Compliant Matrix for Humanizing Productivity - Category 5: Teaching and Learning - Samsudin, Nurhusna; Md Dahlal, Norazilawati; Hashim, Yumi Zuhanis Has-Yun; Ali, Mohammed Farid (2021)
This training slide is part of the Shari'ah-compliant appraisal matrix that focus on Teaching and Learning elements. As a core element of higher learning institutions, Teaching and Learning adopts a more systematic and holistic approach in the provision of humanising education.